Acne mimickers: Differential diagnosis of open comedones - A short review - Santhanakrishnaan Soundarya; Thomas Jayakar (Our Dermatology Online, 2023)
Acne vulgaris is one of the most common disorders of the pilosebaceous unit, affecting around 9.4% of the global population. The principal or preliminary lesions of acne are comedones, which represent the follicular dilation and hypercornification secondary to androgen hypersensitivity. Although the diagnosis of acne is rarely difficult for an experienced dermatologist, we rarely come across various other dermatoses that clinically resemble comedones yet have a different pathophysiology and poorly respond to treatment. Not all disorders that have comedone-like lesions are acne. These disorders should be kept in mind when comedones occur in an unusual site, age, or pattern. This review article mainly focuses and highlights the salient features of multiple non-acne disorders that present with open comedone-like lesions along with an approach to the diagnosis and its management.